Penentuan Kombinasi Produk yang Optimal untuk Meningkatkan Laba pada CV Optima Semarang - Suprapti, Indri; Bodroastuti, Tri (Jurnal Ilmiah Aset, 2012)
CV Optima is one of a wood-based furniture industry which products are variety of table and chair. Its market has reached inter-islands of Java as well as throughout Indonesia. The purpose of my research was to determine optimal combination to increase the revenue of CV Optima Semarang. My research used purposive sampling methodology for collecting the data, namely, all of the company products during one production period (June 2012). Furthermore, the data, which was the documentation of the production based on secondary data of the company, was used to complete my research. The analyzing technique that was used in my research was linear programming by using graphic methodology. The survey result showed that the company needed to produce 150 tables and 400 chairs during one month production. Asa result, the company would be able to generate revenue of Rp. 11.720.000,- in one production period.